Cardiovascular Disease Pattern of Admitted Cases In Medical Ward in 2002 At SGNHC - Sharma, Deewakar; Chaulagain, CP (Nepalese Heart Journal, 2003)
Cardiovascular disease accounts for nearly half of all deaths in developed countries. In developing countries, though communicable diseases still possess the major threat, cardiovascular diseases are rising at an alarming rate. About a quarter of total annual death is caused by cardiovascular disease in developing world. Rheumatic heart disease is considered “disease of the poor’ and is already a big burden in developing countries. But the markedly increased incidence of coronary artery disease in these recent years has alarmed the health care professionals of developing countries. Increasing trend of cardiovascular mortality and morbidity and changing pattern of cardiovascular disease have forced us to look into this matter more seriously.